The Influence of the Game-Based Learning Model on the Learning Interest and Learning Activity of Fifth Grade Students at SD Negeri 058107 Sei Dendang - Gustari, Natasya; Nazaruddin, Ilham; Fatmawati, Fatmawati (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study is useful to determine the effect of the Game Based Learning (GBL) Model on the learning interest and learning activity of fifth grade students at SD Negeri 058107 Sei Dendang. The low learning interest and learning activity of students at the elementary school have become a concern, which is often caused by conventional learning that is less interesting and interactive. GBL is believed to be an innovative approach by integrating game elements to create exciting and participatory learning activities. This study will use a digital educational game based on Wordwall in the Mathematics subject of Fractions. The sample of this study consisted of 30 students in class V/A and 30 students in class V/B. Data processing techniques were carried out in two ways, namely descriptive methods and statistical methods. This study resulted in (1) The learning interest of classes using the GBL model was higher than with the conventional model (F count = 2.142 and a significant value of 0.000 < 0.05); (2) The learning activity of classes using the GBL model was higher than with the conventional model (F count = 0.032 and a significant value of 0.003 < 0.05).